2020
DOI: 10.3389/fcell.2020.00542
|View full text |Cite
|
Sign up to set email alerts
|

A New Animal Model for Pathological Subcutaneous Fibrosis: Surgical Technique and in vitro Analysis

Abstract: Fibrosis is a condition that affects the connective tissue in an organ or tissue in the restorative or responsive phase as a result of injury. The consequences of excessive fibrotic tissue growth may lead to various physiological complications of deformity and impairment due to hypertrophic scars, keloids, and tendon adhesion without understating the psychological impact on the patient. However, no method accurately quantifies the rate and pattern of subcutaneous induced hypertrophic fibrosis. We, therefore, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Aarabi et al [1] established a hypertrophic scar-forming model in mice using a tension-loading device, showing that scar tissues in the skin can develop even in mice. In other cases, fibrous granulation lesions were induced by prolonged inflammation by talc [23] and bleomycin [5,22]. However, inflammation may be an additive factor for fibrosis in scarring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aarabi et al [1] established a hypertrophic scar-forming model in mice using a tension-loading device, showing that scar tissues in the skin can develop even in mice. In other cases, fibrous granulation lesions were induced by prolonged inflammation by talc [23] and bleomycin [5,22]. However, inflammation may be an additive factor for fibrosis in scarring.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, Aarabi et al [1] established a hypertrophic scar-forming mouse model using a biomechanical loading device. Marchesini et al (2020) [23] created a foreign body reaction-associated fibromuscular granulation tissue in rats. Moreover, Cameron et al (2014) [5] created a hypertrophic scar model using bleomycin infusion in mice.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Moreover, it has been confirmed that fibrosis is closely associated with the formation of HS. 2 , 3 At present, anti-metabolite drugs can inhibit scar formation following surgery; however, the use of these drugs may result in certain complications, including the formation of bubble fistula. 4 Therefore, it is necessary to explore safe and effective methods for the prevention of the formation of HS following glaucoma surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Scar lesions are hardly developed in rodents unless devices and chemicals are used 21 23 . However, we have established the wound healing model by excising a part of the abdominal wall in mice without any device or chemical, in which scar lesion and muscle regeneration simultaneously occur in the granulation tissue.…”
Section: Introductionmentioning
confidence: 99%